Treatment with methotrexate carried in lipid core nanoparticles prevents the development of diastolic dysfunction in septic rats. (25th November 2020) - Lopes, N.M; Guido, M.C; Albuquerque, C.I; Jensen, L; Miura, V.M; Marinho, L.M; Maranhao, R.C
Abstract: Introduction: In the development of sepsis, besides the dysregulation of the immune system and disturbances of several vital organs, life-threatening cardiac dysfunction often occurs. Previously, we showed that non-protein nanoparticles that resemble the lipid structure of low-density lipoprotein, termed LDE, concentrate in inflammatory sites. When incorporated in LDE, the cellular uptake of MTX increases several-fold compared to the uptake of commercial MTX. The novel LDE-MTX formulation was shown to have the ability to modulate the immune response in in rabbits with atherosclerosis and in rats with myocardial infarction. LDE-MTX reduced the inflammation and improved the post-infarction cardiac function by increasing the release of angiogenesis, thereby improving hypoxia. The aim of the current study was to test the hypothesis whether LDE-MTX could also improve the cardiac status in septic rats. Methods: Septicemia was induced in Wistar rats by two I.P. injections of lipopolysaccharide (LPS, 10mg/kg) administered with a 24h interval. Rats were allocated to control group (CT, without sepsis; n=5) and 3 groups with sepsis: LDE (n=7), treated with LDE only; MTX (n=6), with commercial MTX (1mg/kg); and LDE-MTX (n=7), with LDE-MTX (1mg/kg). Echocardiography was performed 72h after sepsis induction. Animals were euthanised and LV tissues were collected for protein expression analysis of inflammatory, apoptotic, angiogenesis, hypoxia and adenosine bioavailability markers. Results: Septic rats treated with LDE developed diastolic dysfunction and presented decreased diastolic volume and diameter of the LV. Treatment with LDE-MTX totally prevented the appearance of diastolic dysfunction and the alterations in LV diastolic dilation. Also, LDE-MTX treatment elicited cardiac hypertrophy through the increase of the thickness of septum and of the LV posterior wall. LDE-MTX increased LV mass and the relative heart weight, as compared to the other 3 groups. There were no differences in the protein expression of inflammatory (lymphocytes, tumor necrosis factor, interleukins) and apoptotic (caspases and B-cell lymphoma family) markers among the four groups. However, LDE-MTX showed higher expression of CD68 (macrophage marker). Angiogenesis was higher, while cellular hypoxia was lower in LDE-MTX, respectively represented by vascular endothelial growth factor (VEGF) and hypoxia-inducible factor 1 alpha, in comparison to the other 3 groups. The intracellular adenosine bioavailability was increased in LDE-MTX-treated animals, as promoted by the higher expression of the A1 receptor, as compared to CT. Conclusion: The treatment with LDE-MTX was successful in precluding the appearance of the cardiac dysfunction associated to sepsis. This outcome was conceivably attained by different effects of the treatment observed here, such as those on angiogenesis, macrophage recruitment and adenosine bioavailability in the LV. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): FAPESP (Fundacao de Amparo a Pesquisa do Estado de Sao Paulo)